2016
DOI: 10.1373/clinchem.2016.258897
|View full text |Cite
|
Sign up to set email alerts
|

Fasting Is Not Routinely Required for Determination of a Lipid Profile: Clinical and Laboratory Implications Including Flagging at Desirable Concentration Cutpoints—A Joint Consensus Statement from the European Atherosclerosis Society and European Federation of Clinical Chemistry and Laboratory Medicine

Abstract: AIMS:To critically evaluate the clinical implications of the use of non-fasting rather than fasting lipid profiles and to provide guidance for the laboratory reporting of abnormal non-fasting or fasting lipid profiles. METHODS AND RESULTS:Extensive observational data, in which random non-fasting lipid profiles have been compared with those determined under fasting conditions, indicate that the maximal mean changes at 1-6 h after habitual meals are not clinically significant [ϩ0.3 mmol/L (26 mg/dL) for triglyce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
125
1
4

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 158 publications
(148 citation statements)
references
References 48 publications
6
125
1
4
Order By: Relevance
“…Lipid and lipoprotein concentrations are traditionally measured in fasting blood samples; however, triglyceride concentrations seem to be a better predictor of risk when measured in non-fasting blood samples [38,39,40]. Fasting and non-fasting lipid, lipoprotein and Apo levels seem to be valuable for risk prediction [41,42]. Compared to measuring HDL-C and LDL-C, Apo assays are expensive and not widely available in the clinic.…”
Section: Discussionmentioning
confidence: 99%
“…Lipid and lipoprotein concentrations are traditionally measured in fasting blood samples; however, triglyceride concentrations seem to be a better predictor of risk when measured in non-fasting blood samples [38,39,40]. Fasting and non-fasting lipid, lipoprotein and Apo levels seem to be valuable for risk prediction [41,42]. Compared to measuring HDL-C and LDL-C, Apo assays are expensive and not widely available in the clinic.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, falsely lower nonfasting LDL-C levels could potentially result in insufficient lipid lowering treatment. This problem is addressed in the consensus statement by Nordestgaard et al and judged as probably non-significant in clinical practice (6). We have previously recommended calculating LDL-C in the fasting state to determine lipid lowering intensity in order to prevent undertreatment (7).…”
Section: Tgs: Daytime Rise and Fall And Its Effect On Ldl-cmentioning
confidence: 99%
“…Prospective studies and meta-analyses have consistently demonstrated that non-HDL-C and apo B are least as good as or superior to LDL-C in the prediction of CVD during lipid-lowering therapy (7). Another advantage of non-HDL-C and apo B over LDL-C is the fact that apo B measurements are not influenced by the prandial state and non-HDL-C only slightly (6).…”
Section: Tgs: Daytime Rise and Fall And Its Effect On Ldl-cmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2016, the European Atherosclerosis Society and the European Federation of Clinical Chemistry and Laboratory Medicine presented a similar recommendation with regard to the clinical significance of non-fasting lipid profile 20, 21) . They recommended that laboratory reports should flag abnormal values of serum lipids for non-fasting samples ( Table 1 ).…”
mentioning
confidence: 98%